Design and synthesis of spirobiisoxazoline dibenzoquinone derivatives via [3 + 2] double 1, 3-dipolar cycloaddition reaction. Issue 6 (7th February 2019) - Swapnaja, K. Jones M.; Yennam, Satyanarayana; Chavali, Murthy
Graphical abstract: Highlights: Novel spirobiisoxazoline dibenzoquinone derivatives were synthesized. [3 + 2] Double 1, 3-dipolar cycloaddition was performed using allenoate and nitrile oxide. The new molecules were successfully separated and characterized. Abstract: " A series of novel spirobiisoxazoline dibenzoquinone derivatives were synthesized starting from 2, 5-dimethoxybenzaldehyde in a six-step synthetic sequence". The key step [3 + 2] double 1, 3-dipolar cycloaddition of oxime chloride with allenoate was performed under mild reaction conditions using sodium carbonate at ambient temperature. This is the first innovative synthesis of Spirobiisoxazoline Dibenzoquinone system where quinone ring is alkylated to isoxazoline moiety.